Purification of Phycocyanin from Spirulina platensis Using Natural Deep Eutectic Solvents with Varied Hydrogen Bond Donor - Tentua, Eirene; Hardiningtyas, Safrina Dyah; Setyaningsih, Iriani (Faculty of Fisheries and Marine Universitas Airlangga, 2025)
Graphical Abstract Highlight Research NaDES-based purification offers a sustainable and cost-effective method for extracting phycocyanin from Spirulina platensis. ChCl:Citric Acid (NaDES) achieved 2.3-fold purity (71.83%), surpassing ammonium sulfate precipitation (70.15%). Phycocyanin retained its structural integrity, with enhanced antioxidant activity (IC50 = 40.54 ppm) post-purification. The aqueous two-phase system (ATPs) efficiently separated impurities, improving extraction scalability. This method supports applications in nutraceuticals, cosmetics, and functional food industries as a green alternative. Abstract Phycocyanin, a pharmacologically potent blue pigment extracted from Spirulina platensis, requires optimal purity for effective utilization. Traditional purification methods, although effective, are impeded by time and cost constraints. Addressing this challenge, aqueous two-phase systems (ATPs) incorporating natural deep eutectic solvents (NaDES) emerge as promising alternatives. These systems offer operational simplicity and cost-effectiveness, ensuring efficient purification with high purity and optimal recovery of phycocyanin. This study investigated the impact of various types of hydrogen bond donors (HBD) within choline chloride-based natural deep eutectic solvents (NaDES) on the purification of phycocyanin. Phycocyanin was extracted from Spirulina platensis biomass through ultrasonication and purified using an aqueous two-phase system with various HBD of NaDES, including urea, glycerol, and citric acid. The experimental design adhered to a completely randomized design. The initial purity index and yield of crude extract phycocyanin were 0.54±0.02 and 12.79±0.27%, respectively. The NaDES system with ChCl:citric acid exhibited superior performance, demonstrating a high purity index and recovery (2.3-fold, 71.83±2.36%) compared to ammonium sulfate (1.5-fold, 70.15±4.10%). The obtained phycocyanin was partially pure compared to commercial phycocyanin (purity index: 1.60), as indicated by SDS-PAGE. Moreover, the antioxidant activity of phycocyanin was enhanced post-purification, evident in the IC50 value of 40.54 ppm. In summary, organic acid-based NaDES has proven effective in increasing the purity and achieving a significant recovery percentage of phycocyanin compared to conventional ammonium sulfate methods. The antioxidant activity of phycocyanin was enhanced after purification. These results indicate the promising potential of NaDES-based ATP systems for producing functional protein-based ingredients, exemplified by phycocyanin.